Formulasi Sosis Ikan Tuna dan Hati Ayam sebagai Pangan Alternatif Pencegahan Stunting dan Anemia pada Balita - Rahmawati, Lusi Anindia; Umami, Zakia; Komalasari, Ema; Rinaldy, Nadya; Iskandar, Suhayhoa Jaceyntha Sarah (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2025)
Stunting is a chronic nutritional deficiency issue that can lead to growth and development disorders in children. Children suffering from stunting are also likely to have significantly lower hemoglobin levels. This study aims to analyze the effect of adding tuna fish and chicken liver on the nutrient content of sausage food products and to assess the acceptance of the sausages among semi-trained panelists at Al-Azhar University Indonesia. The research was conducted using an experimental method with 33 panelists, employing a Completely Randomized Design (CRD) with three treatment levels. The results of the hedonic sensory analysis and hedonic quality were analyzed using One-Way ANOVA. The hedonic test results showed significant differences (p<0.05) in all parameters: taste, texture, aftertaste and overall acceptance. The hedonic quality test also indicated significant differences (p<0.05) in the same parameters. The selected formula based on the MPE test was formula F1, consisting of 35% chicken liver and 65% tuna fish. Nutritional analysis of formula F1 revealed energy content of 155 kcal, protein 12.5 g, total fat 2.6 g, total carbohydrates 20.4 g, moisture content 62.6%, ash content 1.9%, and iron content 3.5 mg. The F1 sausage formula can be considered a high-iron and high-protein food for toddlers aged 1 to 3 years.Keywords – Chicken Liver, High Protein, Sausage, Stunting, Tuna Fish.